Perceptions of the Effect of COVID-19 on the Health of Mapuche Young Adults in Chile - Olivella-Cirici, Marc; Molina, Xaviera; Maass Olea, Maria Jesús; Vanegas-López, Jairo; Correa Matus, Eliana; Pasarín, M Isabel; Muñoz-Poblete, Claudio; Pérez, Gloria (The International Indigenous Policy Journal, 2025)
We aimed to investigate the perceptions of Mapuche young adults in Araucanía, Chile, regarding the impact of the COVID-19 pandemic on their communities, adherence to restrictions, and coping responses. Eight Mapuche individuals were included in this qualitative study, segmented by gender. Interviews with a semi-structured script were carried out between February and May 2023. A thematic analysis of the discourse was used with subsequent triangulation and validation of the results. The people interviewed believed that, although the pandemic affected their communities, this challenge strengthened ties and contributed to the recovery of the ancestral worldview. There was a temporal dynamic in adherence to restrictions, with initial distrust but high compliance, including vaccination. There was complementarity between Western and traditional Mapuche medicine, which highlights the importance of intercultural health strategies. The pandemic had an impact on young Mapuche adults by altering community dynamics and cultural practices, with the potential to exacerbate inequalities in their communities. This study emphasizes the need to integrate the indigenous worldview in decisions about restrictions and advocates considering cultural diversity in future health crises.